Analisis Kinerja Keuangan pada Koperasi Karyawan Pertamina Lapangan Kamojang (Koperlak) Kabupaten Bandung - K, Kurnaeli (Fakultas Ekonomi Universitas Garut, 2016)
The number of cooperatives in Indonesia is one of the largest in the world, but its contribution is still lacking for the community. The financial performance of cooperatives is one of the things that needs to be highlighted, because by knowing the financial performance of a cooperative, it can be seen how good performance is for the progress of the cooperative which will also have an impact on society. This research was conducted to determine the financial performance of the Pertamina Field Kamojang Employee Cooperative (KOPERLAK) Kab. Bandung for the period 2011-2015. Tools used in analyzing this financial performance using ratio analysis, namely analysis of liquidity ratios, analysis of solvency ratios, and analysis of profitability ratios. The data used are the financial statements of the Pertamina Field Kamojang Employee Cooperative (KOPERLAK) Kab. Bandung for the period 2011-2015. To determine the level of liquidity using the calculation of Current Ratio and Cash Ratio. To determine the level of solvency using the calculation of the Debt To Total Assets Ratio and Debt To Equity Ratio. To determine the level of profitability using the calculation of Return On Investment and Return On Equity. The object of this research is Pertamina Field Kamojang Employee Cooperative (KOPERLAK) Kab. Bandung. The analytical method used is a descriptive method with a qualitative approach. The results of this study indicate that the Current Ratio is in a healthy condition, meaning that the current assets of the cooperative can guarantee its short-term liabilities (liquid), the Cash Ratio is in an unhealthy state, which means that cash and cooperative banks cannot guarantee their short-term liabilities (ilikuid), Debt To The Total Assets Ratio is in an unhealthy state, meaning that the total assets of the cooperative have not been able to guarantee the total debt of the cooperative (insolvable), the Debt To Equity Ratio is in an unhealthy state, meaning that the total capital of the cooperative has not been able to guarantee the total debt of the cooperative (insolvable), Return on Investment Being in an unhealthy condition means that the cooperative has not been able to use assets productively to produce maximum residual results, and Return On Equity is in a healthy condition, which means that the capital owned by the cooperative can produce maximum residual results of operations.